Research on Suppression of Vibration Caused by Combustion Pressure Pulsation in Aircraft Engines - Liang Hong; Chao-Ping Zang; He-Jiong Ji; Qiu-Xia Yu; Yun-Fan Jiang; Lian Shen (Shock and Vibration)
Abnormal high-energy narrowband signals appeared in the aircraft engine test. By analyzing the characteristics of the vibration signals and the pressure pulsation signals in the measurement point data of the engine, it can be speculated that the abnormal vibration energy of the engine is not related to the operation of rotating parts, which upends a conventional wisdom on aeroengine’s vibration, i.e., mainly coming from rotor excitations. A special measurement test for the pulsation of the main combustion chamber components was designed. The pulsation characteristics, which exhibit a fixed ratio between the vibration/pulsation frequency value and the sound velocity during combustion chamber operation, of the main combustion chamber during component testing are similar to those under actual working conditions, which conform to the characteristics of plane wave theory. A three-dimensional acoustic fluid finite element model was established to simulate the two stream flow in the main combustion chamber. The simulation results showed that the acoustic modal eigenvalues of the secondary flow path outside the main combustion chamber were consistent with the pulsation/vibration characteristics in the aircraft engine and component tests, proving that the main combustion chamber is the excitation source of the abnormal high-energy narrow frequency vibration. By adjusting the air/fuel equivalence ratio at the head of the combustion chamber flame tube, the working conditions of the combustion chamber were optimized. Then, according to the results through the main combustion chamber component tests and overall machine tests, the narrow frequency high-energy components in the airflow pulsation and overall machine vibration disappeared, which meant that the vibration of the aircraft engine was effectively suppressed. This investigation successfully achieved the positioning of the high-energy vibration source in the aircraft engine and the vibration energy suppression of the excitation source under minimum engineering costs. Moreover, the suppression method for vibration caused by the combustion pulsation, which is proposed in this paper, can provide technical guidance for solving similar problems in practical applications.